Health economic evaluations comparing insulin glargine with NPH insulin in patients with type 1 diabetes: a systematic review - Hagenmeyer, Ernst-Günther (BioMed Central, 2011)
BACKGROUND: Compared to conventional human basal insulin (neutral protamine Hagedorn; NPH) the long-acting analogue insulin glargine (GLA) is associated with a number of advantages regarding metabolic control, hypoglycaemic events and convenience. However, the unit costs of GLA exceed those of NPH. This study aims to systematically review the economic evidence comparing GLA with NPH in basal-bolus treatment (intensified conventional therapy; ICT) of type 1 diabetes in order to facilitate informed decision making in clinical practice and health policy. METHODS: A systematic literature search was performed for the period of January 1st 2000 to December 1st 2009 via Embase, Medline, the Cochrane Library, the databases GMS (German Medical Science) and DAHTA (Deutsche Agentur für Health Technology Assessment), and the abstract books of relevant international scientific congresses. Retrieved studies were reviewed based on predefined inclusion criteria, methodological and quality aspects. In order to allow comparison between studies, currencies were converted using purchasing power parities (PPP). RESULTS: A total of 7 health economic evaluations from 4 different countries fulfilled the predefined criteria: 6 modelling studies, all of them cost-utility analyses, and one claims data analysis with a cost-minimisation design. One cost-utility analysis showed dominance of GLA over NPH. The other 5 cost-utility analyses resulted in additional costs per quality adjusted life year (QALY) gained for GLA, ranging from € 3,859 to € 57,002 (incremental cost effectiveness ratio; ICER). The cost-minimisation analysis revealed lower annual diabetes-specific costs in favour of NPH from the perspective of the German Statutory Health Insurance (SHI). CONCLUSIONS: The incremental cost-utility-ratios (ICER) show favourable values for GLA with considerable variation. If a willingness-to-pay threshold of £ 30,000 (National Institute of Clinical Excellence, UK) is adopted, GLA is cost-effective in 4 of 6 cost utility analyses (CUA) included. Thus insulin glargine (GLA) seems to offer good value for money. Comparability between studies is limited because of methodological and country specific aspects. The results of this review underline that evaluation of insulin therapy should use evidence on efficacy of therapy from information synthesis. The concept of relating utility decrements to fear of hypoglycaemia is a plausible approach but needs further investigation. Also future evaluations of basal-bolus insulin therapy should include costs of consumables such as needles for insulin injection as well as test strips and lancets for blood glucose self monitoring.